Explorando o outro lado: percepção paterna de práticas parentais positivas e negativas - Accica, Thais Fernanda (Universidade Federal de São Carlos, 2024)
Research on parenting styles demonstrates that parents who are communicative and affectionate in their interactions with their children and who, at the same time, set clear and consistent boundaries, promote a favorable environment to the development of children who become more confident and who have more self-control later in life. On the other hand, punitive practices, especially those that include physical punishment (e.g., spanking) are associated with low self-esteem in mid- and long-term. Few studies, however, have explored fathers’ perspective on both positive and negative effects of parenting practices. The study aimed to contribute in this direction by asking fathers to share their beliefs on parental educational practices. Fifty-three fathers of children aged 5 to 12 years participated in the present study by responding to a questionnaire on the Google Forms platform. The first part of the form was the Parenting Styles Inventory (PSI) and the second part included questions about parenting practices. Twenty-five participants (47.2%) had final PSI scores indicating a great parental style, however, qualitative data pointed to a discourse that is inconsistent with positive parental practices. Data analysis also revealed fathers' wish to be heard, in particular, on what raising children is concerned.
Exploring the other side: fathers' perspective on positive and negative parental practices
Keywords: Estilos parentais; Percepção paterna; Práticas parentais; Parental styles; Fathers' perspective; Parental practices; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO::PROCESSOS PERCEPTUAIS E COGNITIVOS; DESENVOLVIMENTO